Electric measurements with constant current: A practical method for characterizing dielectric films - Giacometti, J. A.; Wisniewski, C.; Ribeiro, P. A.; Moura, W. A. (American Institute of Physics (AIP), 2001)
This article assesses the use of the constant current (CC) method for characterizing dielectric films. The method is based on charging the sample with a constant current (current stress) and measuring the corresponding voltage rise under the closed circuit condition. Our article shows that the CC method is an alternative to the constant voltage stressing method to study the electric properties of nonpolar, ferroelectric, and polar polymers. The method was tested by determining the dielectric constant of polytetrafluoroethylene, and investigating the electric conduction in poly(ethylene terephthalate). For the ferroelectric polymer poly(vinylidene fluoride), it is shown that hysteresis loops and the dependence of the ferroelectric polarization on the electric field can be obtained. (C) 2001 American Institute of Physics.